Respiratory Syncytial Virus: An Uncommon Cause of Febrile Seizures-Results from a Systematic Review and Meta-Analysis - Matteo Riccò; Milena Pia Cerviere; Silvia Corrado; Silvia Ranzieri; Federico Marchesi (MDPI AG, 2022)
Human Respiratory Syncytial Virus (RSV) is a highly contagious viral pathogen. In infants, it is usually listed among the main causes of medical referrals and hospitalizations, particularly among newborns, and a considerable base of evidence associates RSV infections and bronchiolitis with long-term neurological sequelae. We specifically performed a systematic review and meta-analysis in order to ascertain whether RSV infections may be associated with an increased risk for febrile seizures (FS) in infected infants. According to the PRISMA statement, Pubmed, Embase, and pre-print archive medRxiv.og were searched for eligible observational studies published up to 1 July 2022. Raw data included the incidence of FS among children admitted for influenza-like illness (ILI) and/or bronchiolitis, with a confirmed diagnosis of RSV or seasonal influenza virus (SIV) infection. Data were then pooled in a random-effects model. Heterogeneity was assessed using the I2 measure, while reporting bias was assessed by means of funnel plots and regression analysis. A total of 11 studies including 6847 cases of RSV infections were retrieved, with a pooled prevalence of 29.975 cases of FS per 1000 RSV cases (I2 = 88.5%). The prevalence was not substantially greater in studies performed in pediatric intensive care units (53.817 per 1000 RSV cases vs. 23.552, p = 0.12). Higher occurrence of FS was reported from studies performed after 2010 (Risk Ratio [RR] 1.429, 95% Confidence Interval [95%CI] 1.049-1.948), and in China (RR 2.105, 95%CI 1.356-3.266) and South Africa (RR 1.722, 95%CI 1.060-2.824) than in Europe, while a lower occurrence was reported form the USA (RR 0.414, 95%CI 0.265-0.649). Eventually, FS were less likely reported from RSV cases compared to subjects affected by seasonal influenza (RR 0.402; 95%CI 0.228-0.708). Although RSV is often associated with high risk of neurological complications, substantially less cases of FS are reported than in SIV infections. However, the paucity of available studies recommends a cautious appraisal of aforementioned results.